(untitled) (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
In our study, we determined the biochemical and biological activity and toxicity of Artemisia sieversiana Willd., which grows in Mongolia. The amount of moisture, acidity, protein, oil, total and crude carbohydrates, vitamins and secondary metabolites in the dry weight of the plant was determined. A group of extracts was taken out and the chemical compounds of each group were identified by thin layer chromatography, and antioxidant activity was determined, IC50 value was calculated. IC50 values were calculated for hexane extract >200 μg/ml, chloroform extract 62.2 μg/ml, ethyl-acetate extract 54.8 μg/ml, n-butanol extract 55.9 μg/ml, aqueous extract 84.34 μg/ml. Ethylacetate, chloroform and hexane extracts showed growth inhibition zones for S.aureus ATCC2592 and B. subtilis ATCC6633. Each group of extracts was prepared at four different concentrations and the toxicity to Artemia salina crab larvae was determined and the LC50 value was calculated by Clarkson’s toxicity index. Cеверсийн шарилж (Аrtemisia sieversiana Willd.)-ийн хандны биологийн идэвх, хорон чанарын судалгаа Хураангуй: Бид судалгаандаа Монгол оронд ургадаг Северсийн шарилж (Artemisia sieversiana Willd.)-ийн биохими болон биологийн идэвх, хорон чанарыг тодорхойлов. Үүнд ургамлын хуурай жинд чийг, хүчиллэг, уураг, тос, нийт болон ангижирсан нүүрс ус, витамин, хоёрдогч метаболитуудийн хэмжээг тодорхойлов. Бүлэг хандуудыг гарган авч нимгэн үеийн хроматографийн аргаар бүлэг ханд тус бүрийн химийн нэгдлүүдийг таньж, антиоксидант идэвхийг тодорхойлон IC50 утгыг тооцоход гексан ханд >200 мкг/мл, хлороформын ханд 62.8 мкг/мл, этил-ацетатын ханд 54.8 мкг/мл, н-бутанолын ханд 55.9 мкг/мл, усан ханд 84.34 мкг/мл. Этил-ацетат, хлороформ, гексан ханд S.aureus ATCC2592, B.subtilis ATCC6633 бактерийн өсөлтийг дарангуйлах ариун бүс үүсгэв. Бүлэг ханд тус бүрийг дөрвөн өөр концентрацтайгаар бэлтгэж хорон чанарыг Artemia salina хавчийн авгалдайд тодорхойлон, LC50 утгыг тооцож Кларксоны хорон чанарын индексээр үнэлэхэд этилацетатын ханд 414.43 мкг/мл буюу дунд зэргийн хортой бусад ханд хоргүй байв. Түлхүүр үг: Brine shrimp, царван, S.aureus, ургамлын хоёрдогч метаболит, шарилж